Science-Policy Interfaces As A Green Agri-Food System Development Incentives - Asatryan, Hovhannes; Grigoryan, Hrachya (ՀՀ ԳԱԱ ՏԻ)
Current global developments (including global warming, climate change, and its hazards, the unstable political situation in the region, the consequences of the COVID-19 pandemic, and environmental issues) bring us to the need for sustainable economic development and the formation of a green economy. Both green economy and green agriculture in Armenia have a long way to go and require some preconditions such as the formation of social, political, and economic bases and necessary policy framework. Текущие глобальные события (включая глобальное потепление, изменение климата и его опасности, нестабильную политическую ситуацию в регионе, последствия пандемии COVID-19 и экологические проблемы) подводят нас к необходимости устойчивого экономического развития и формирования зеленой экономики. Ներկայիս գլոբալ զարգացումները (գլոբալ տաքացումը, կլիմայի փոփոխությունները և դրանով պայմանավորված վտանգները, տարածաշրջանում անկայուն քաղաքական իրավիճակը, COVID-19 համավարակի հետևանքները և բնապահպանական հիմնախնդիրները) բերում են կայուն տնտեսական զարգացման և կանաչ տնտեսության ձևավորման անհրաժեշտությանը:
Keywords: State policy